2019
DOI: 10.2147/ott.s197559
|View full text |Cite
|
Sign up to set email alerts
|

<p>Completely resolved advanced biliary tract cancer after treatment by pembrolizumab: a report of two cases</p>

Abstract: Biliary tract cancers (BTC) represent an aggressive disease with a dismal prognosis. Gemcitabine in combination with cisplatin is the standard first-line palliative treatment for advanced BTC. There is no established treatment following progression on gemcitabine-cisplatin. In this article, we present two cases for individuals with advanced BTC who were treated with pembrolizumab and the tumors have completely resolved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 25 publications
(28 reference statements)
0
12
0
Order By: Relevance
“…Of note, none of the patients across the two studies were MSI [92]. Interestingly, two cases of complete disease resolution were reported after pembrolizumab alone in second-line treatment [94].…”
Section: Ici Monotherapymentioning
confidence: 94%
“…Of note, none of the patients across the two studies were MSI [92]. Interestingly, two cases of complete disease resolution were reported after pembrolizumab alone in second-line treatment [94].…”
Section: Ici Monotherapymentioning
confidence: 94%
“…53,54 These findings are supported by case reports, which also detail profound and prolonged responses to ICIs in patients with CCA and known MSI or MMR deficiency, high TMB, or high rates of insertion or deletion mutations, which can result in neoantigens. [77][78][79][80][81] However, in microsatellite-stable, non-MMR deficient CCA, the ORR to ICI monotherapy appears much lower, though data are mixed. To date, KEYNOTE-158 (NCT02628067) is the largest study of ICI monotherapy with pembrolizumab; it includes patients with advanced biliary cancers without known MMR deficiency, after progression on or intolerance to at least 1 line of standard therapy.…”
Section: Tumour Immune Microenvironmentmentioning
confidence: 99%
“…( 54 ) Although current studies on immunotherapy in CCA are limited, pembrolizumab, which is an anti‐PD‐1 antibody, showed promising results in patients with advanced CCA and is approved for microsatellite instability/mismatch unresectable or metastatic solid cancers, including hepatobiliary cancers. ( 61,62 ) A study using laser capture microdissection with 78 iCCA cases has identified four immune subtypes in the tumor microenvironment. ( 63 ) These subtypes had different populations and profiles of infiltrating cells as well as different gene expression profiles in inflammatory and immune checkpoint pathways, indicating that effects of immunotherapy such as PD‐1 antibodies may be limited to a certain percentage of patients with CCA.…”
Section: Functional Roles Of the Cca Microenvironmentmentioning
confidence: 99%